Contribuições da teoria das restrições para gestão da mudança - Ducatti, Ana Paula Silva [UNESP] (2014)
The literature on change management (GM) presents great diversity of models, commonly ranked prospects in content, context, process and individual differences. Starting from the same asumptions that led to their applications in other fields of knowledge, the Theory of Constraints (TOC) presents a particular view of how to deal with changes. From own tools, TOC seeks to find the focus of change and eliminate resistence, communicating the change logically. Given the paucity of studies that assess the way the TOC deals with GM, through a literature review aims to identify and analyze the potential contributions of TOC to the field of knowledge management to organizational changes. To do so, we attempted to systematize the existing knowledge about GM, proposing a Framework. This framework is used as a basis to challenge the more traditional perspectives of GM with those identified with TOC. The results of this comparison allowed the identification of similarities and differences of purpose between traditional views and TOC, as well as practical tools to support the process of change. Although important purposes of convergence between the more traditional forms of GM and TOC have been identified, there are significant differences which give rise leads to complement each others. We conclude that, focus on side of change of its tools to the process are the main contributions of TOC to traditional GM models. In addressing the contributions that TOC can bring to the processes of GM, as well as to identify gaps that can potentially compromise it, this article discusses the GM from the perspective of high potential pionner, helping to expand your knowledge base